2010
DOI: 10.1155/2010/956304
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor-Engineered T Cells for Immunotherapy of Cancer

Abstract: CD4+ and CD8+ T lymphocytes are powerful components of adaptive immunity, which essentially contribute to the elimination of tumors. Due to their cytotoxic capacity, T cells emerged as attractive candidates for specific immunotherapy of cancer. A promising approach is the genetic modification of T cells with chimeric antigen receptors (CARs). First generation CARs consist of a binding moiety specifically recognizing a tumor cell surface antigen and a lymphocyte activating signaling chain. The CAR-mediated reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
109
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 147 publications
(167 reference statements)
2
109
0
4
Order By: Relevance
“…Over time, CARs with differing signaling domains were developed and termed as first, second, and third generation CARs. 29 The additional signaling domains in second and third generation CARs help to improve their survival in patients. The tremendous clinical success of CD19-specific CAR T cells underlines the high potential of the CAR technology.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, CARs with differing signaling domains were developed and termed as first, second, and third generation CARs. 29 The additional signaling domains in second and third generation CARs help to improve their survival in patients. The tremendous clinical success of CD19-specific CAR T cells underlines the high potential of the CAR technology.…”
Section: Introductionmentioning
confidence: 99%
“…These genetically engineered T-cell constructs combine the antibody-derived antigen-binding motif, known as a single-chain fragment of variable regions (scFv) that recognises the target antigen, with the intracellular functional domains of T-cell receptor (TCR)-related signalling molecules, the CD3ζ-chain, and T-cell costimulatory molecules such as CD28, CD134, and CD137. 4,5 Using lentiviral transduction or electroporation, the genetic constructs are introduced into the autologous peripheral T cells collected by leukapheresis procedures [ Figure 1]. When expressed on T cells, CAR redirects T-cell specificity and cytotoxic immunoreactivity against the cells expressing the targeted antigen epitope.…”
mentioning
confidence: 99%
“…These advances have made possible the creation of second-and third-generation T cells expressing CAR, which are endowed with potent effector functions. [4][5][6][7][8] Thus, several groups have evaluated these second generations of CAR as a potential treatment to kill leukaemic cells in patients with B-cell neoplasms. [17][18][19][20][21][22] As for any targeted immunotherapy, the success of novel genetically engineered T cells relies heavily on the characteristics of the target cell surface antigen.…”
mentioning
confidence: 99%
“…The third generation of CAR incorporated two co-stimulatory molecules: CD28, CD134 or CD137 in a sequence fused to CD3-zeta chain and were designed to further enhance killing functions, proliferation capacities and production of survival cytokines such as interleukin-2. 7,8 Compared to classical T-cell-based immunotherapies, T-cells expressing-CAR present several attractive advantages including obviating the need for recognising peptide presentation by major histocompatibility complex, the ability to target a range of tumour surface antigens, and relatively Leukaemic B-Cells rapid generation within one to four weeks. 5,7,8 Although the clinical value of genetically engineered T-cells is still to be validated, recent data from two studies reported that CAR targeting CD19 (CART19) was able to kill leukaemic B-cells expressing this surface antigen and that tumour control was sustained for 10 months following this therapy.…”
mentioning
confidence: 99%
“…7,8 Compared to classical T-cell-based immunotherapies, T-cells expressing-CAR present several attractive advantages including obviating the need for recognising peptide presentation by major histocompatibility complex, the ability to target a range of tumour surface antigens, and relatively Leukaemic B-Cells rapid generation within one to four weeks. 5,7,8 Although the clinical value of genetically engineered T-cells is still to be validated, recent data from two studies reported that CAR targeting CD19 (CART19) was able to kill leukaemic B-cells expressing this surface antigen and that tumour control was sustained for 10 months following this therapy. 9,10 The CART19 was designed to express a single chain variable fragment derived from an anti-CD19 specific antibody along with a CD137 signalling domain and the CD3zeta-chain.…”
mentioning
confidence: 99%